Catégorisation et vocabulaire spécialisé : enquête sur les dénominations de mouvements sportifs - Angelina Aleksandrova (Lexis: Journal in English Lexicology)
This research puts the question of linguistic categorization back into the context of sports terminology by looking at the translation of English crossfit movement terms (Tmvt) by non-specialist French speakers. The study examines three cases involving simple Tmvts (squat, snatch), compound Tmvts (pull-up, deadlift) and polylexical Tmvts (push jerk, split jerk, push press,…). The analysis of translation errors reveals that accessing the signified of the foreign term mobilizes various linguistic skills depending on the case, and the study of translation strategies (such as calque, transposition, literal translation, or description) provides linguistic clues about the conceptual delimitation of each Tmvt in particular and the organization of the knowledge network of the specialized domain of sports exercises in general.